Correction to: Jejunal pouch reconstruction after total gastrectomy is associated with better short-term absorption capacity and quality of life in early-stage gastric cancer patients - Wei Chen; Xumian Jiang; Hui Huang; Zao Ding; Chihua Li (BMC Surgery, 2018)
Following publication of the original article [1], the authors reported that one of the authors’ names is spelled incorrectly.